Recovery of myocardial perfusion after percutaneous coronary intervention of chronic total occlusions is comparable to hemodynamically significant non‐occlusive lesions. Issue 6 (15th November 2018) - Schumacher, Stefan P.; Driessen, Roel S.; Stuijfzand, Wijnand J.; Raijmakers, Pieter G.; Danad, Ibrahim; Dens, Jo; Spratt, James C.; Hanratty, Colm G.; Walsh, Simon J.; Boellaard, Ronald; van Rossum, Albert C.; Opolski, Maksymilian P.; et al.
Abstract: Background: The benefits of chronic coronary total occlusion (CTO) percutaneous coronary intervention (PCI) are being questioned. The aim of this study was to assess the effects of CTO PCI on absolute myocardial perfusion, as compared with PCI of hemodynamically significant non‐CTO lesions. Methods: Consecutive patients with a preserved left ventricular ejection fraction (≥50%) and a CTO or non‐CTO lesion, in whom [ 15 O]H2 O positron emission tomography was performed prior and after successful PCI, were included. Change in quantitative (hyperemic) myocardial blood flow (MBF), coronary flow reserve (CFR) and perfusion defect size (in myocardial segments) were compared between CTOs and non‐CTO lesions. Results: In total 92 patients with a CTO and 31 patients with a non‐CTO lesion were included. CTOs induced larger perfusion defect sizes (4.51 ± 1.69 vs. 3.23 ± 2.38 segments, P < 0.01) with lower hyperemic MBF (1.30 ± 0.37 vs. 1.58 ± 0.62 mL·min −1 ·g −1, P < 0.01) and similarly impaired CFR (1.66 ± 0.75 vs. 1.89 ± 0.77, P = 0.17) compared with non‐CTO lesions. After PCI both hyperemic MBF and CFR increased similarly between groups ( P = 0.57 and 0.35) to normal ranges with higher hyperemic MBF values in non‐CTO compared with CTO (2.89 ± 0.94 vs. 2.48 ± 0.73 mL·min −1 ·g −1, P = 0.03). Perfusion defect sizes decreased similarly after CTO PCI and non‐CTO PCI ( P = 0.14), leading to small residual defect sizes in both groups (1.15 ± 1.44 vs. 0.61 ± 1.45 segments, P = 0.054). Conclusions: Myocardial perfusion findings are slightly more hampered in patients with a CTO before and after PCI. Percutaneous revascularization of CTOs, however, improves absolute myocardial perfusion similarly to PCI of hemodynamically significant non‐CTO lesions, leading to satisfying results.